Avaliação dos efeitos biológicos gerados em queratinócitos imortalizados (HaCaT) pela exposição a raios X policromáticos e de baixo fluxo - Vasconcelos, Jullyana Mendes (Universidade Federal de São Carlos, 2024)
Sirius, the Brazilian synchrotron accelerator, is capable of investigating matter, especially using X-rays. X-rays have enough energy to ionize matter and end up causing damage to biological materials, which constitute a large part of the samples studied at Sirius. In this work, the biological damage caused in immortalized keratinocytes by X-rays generated in a benchtop source was evaluated. This allowed the development of a sample preparation and evaluation protocol for the biological effects of X-rays, which could later be extended to experiments in the various beamlines of Sirius. The developed sample preparation method consisted of a composition of Iscove’s Modified Dulbecco’s Medium (IMDM) culture medium and agarose, immobilizing culture plates vertically and hydrating and nourishing HaCaT cell lineage. The preparation was successful both technically and biologically, as indicated by the resazurin cell viability test results, showing nourished and viable cells after exposure to the agarose-composed medium. Irradiations were performed using the Mini-X2 X-ray generator, with a voltage of 70 kV and a current of up to 140 μA. The dose rate was determined from computational simulations with the SpekCalc software and validated with thermoluminescent dosimeters (TLD) and optically stimulated luminescence dosimeters (OSLD). The dose rate values resulted in (3.19 ± 0.14) Gy/h without agarose and approximately 1.89 Gy/h with agarose. The dose range used for cell irradiation was from 0 to 4 Gy. The resazurin test indicated that the dose values used were not high enough to generate observable damage to the cells within the tested time frame. With the reactive oxygen species (ROS) assay using the chemical probe DCFH2-DA, a trend of increasing ROS was observed with increasing dose, but the peak production occurred at 2 Gy, while it was expected at 4 Gy. This is eventually attributed to the antioxidant mechanisms of cells, which eliminate ROS instead of storing them linearly. With DAPI assays, a fluorescent DNA marker, and clonogenic assays, it was possible to verify that after 6 days of incubation of initially irradiated cells, there was a decrease in cell proliferation with an increase in the received dose. This indicates that even with relatively low doses, damage can be observed with temporal monitoring. In summary, the results obtained showed that the sample preparation and irradiation effects evaluation protocols can be extended to various beamlines of Sirius, which is crucial for studies involving biological samples.
Evaluation of the biological effects generated in immortalized keratinocytes (HaCaT) by exposure to polychromatic and low-flux X-rays
Keywords: Raios X; Dosimetria; Danos Biológicos; X-rays; Dosimetry; Biological Damages; CIENCIAS EXATAS E DA TERRA::FISICA::FISICA DA MATERIA CONDENSADA::PROP.OTICAS E ESPECTROSC.DA MAT.CONDENS;OUTRAS INTER.DA MAT.COM RAD.E PART.